Existence and Multiplicity of Positive Solutions of a Boundary-Value Problem for Sixth-Order ODE with Three Parameters. (18th August 2010) - Zhang, Liyuan; An, Yukun
Abstract : We study the existence and multiplicity of positive solutions of the following boundary-value problem:- u ( 6 ) - γ u ( 4 ) + β u ′′ - α u = f ( t, u ), 0 < t < 1, u ( 0 ) = u ( 1 ) = u ′′ ( 0 ) = u ′′ ( 1 ) = u ( 4 ) ( 0 ) = u ( 4 ) ( 1 ) = 0, wheref : [ 0, 1 ] × R + →R + is continuous, α, β, andγ ∈ R satisfy some suitable assumptions.